The The Resolution of Weyl Module for Two Rows in Special Case of the Skew-Shape - Abd-Alrida, Shaymaa N.; Hassan, Haytham R. (Iraqi Journal of Science, 2020)
The aim of this work is to survey the two rows resolution of Weyl module and locate the terms and the exactness of the Weyl Resolution in the case of skew-shape (8,6)/(2,1).